A 'third culture' in economics? An essay on Smith, Confucius and the rise of China - Carsten Herrmann-Pillath (Frankfurt School of Finance & Management, 2011)
China's rise drives a growing impact of China on economics. So far, this mainly works via the force of example, but there is also an emerging role of Chinese thinking in economics. This paper raises the question how far Chinese perspectives can affect certain foundational principles in economics, such as the assumptions on individualism and self-interest allegedly originating in Adam Smith. I embark on sketching a 'third culture' in economics, employing a notion from cross-cultural communication theory, which starts out from the observation that the Chinese model was already influential during the European enlightenment, especially on physiocracy, suggesting a particular conceptualization of the relation between good government and a liberal market economy. I relate this observation with the current revisionist view on China's economic history which has revealed the strong role of markets in the context of informal institutions, and thereby explains the strong performance of the Chinese economy in pre-industrial times. I sketch the cultural legacy of this pattern for traditional Chinese conceptions of social interaction and behavior, which are still strong in rural society until today. These different strands of argument are woven together in a comparison between Confucian thinking and Adam Smith, especially with regard to the 'Theory of Moral Sentiments', which ends up in identifying a number of conceptual family resemblances between the two. I conclude with sketching a 'third culture' in economics in which moral aspects of economic action loom large, as well as contextualized thinking in economic policies.
Keywords: B11; B12; Z1; 330; Confucianism; Adam Smith; physiocracy; collectivism and individualism; social relations in China; morality; economy of Imperial China